Enhanced Queue Management Mechanism for Differentiated Services Networks - Albayati, Majid Hamid Ali (2012)
In the Internet, it is supposed that all connections are treated equally in the network. Due to the limitation of network resources are limited, providing guarantees on performance measures imposes declining new connections if resources are not available. Assigning network resources to connections according to their classes requires differentiating between the connection classes. For this reason, the Differentiated Services (DiffServ) has been proposed. Many of the QoS mechanisms have been developed which allow different services carried by the Internet to co-exist. Many of these mechanisms were both complex and failed to scale to meet the demands of the Internet. MRED is the common mechanism used in DifJServ routers. It suflers from large queue length variation and untimely congestion detection and notification. These consequences cause performance degradation due to high queuing delays and high packet loss. In this project, enhanced version of MRED is developed to improve the performance of Diffserv networks that use TCP as the transport layer protocol. Enhanced MRED includes average packet arrival rate when computing the packet drop probability. Enhanced MRED showed a good pedonnance compared to that of MRED, in term of fast congestion detection and notification. The limitation of the new mechanism is that it works only with responsive connections which play a big role in avoiding and controlling the congestion. The major contribution of this project is to provide an improved queue management mechanism for Diffserv networks that responds to congestion more quickly, delivers congestion notification timers, and controls the queue length directly to congestion which results in minimizing queue length variation. All these would help improve the DlffServ networks performance.